2021
DOI: 10.3389/fonc.2021.683605
|View full text |Cite
|
Sign up to set email alerts
|

Novel Prognostic Biomarkers in Metastatic and Locally Advanced Colorectal Cancer: Micronuclei Frequency and Telomerase Activity in Peripheral Blood Lymphocytes

Abstract: PurposeDue to the current practice on colorectal cancer (CRC) management, chemoresistance is most often recognized at the end of the treatment. Therefore, effective and easy-to-use prognostic biomarkers are needed.Experimental DesignWe evaluated the prognostic significance of two novel CRC biomarkers: a) micronuclei frequency (MNf) in 55 metastatic CRC (mCRC) and 21 locally advanced rectal cancer (laRC) patients using cytokinesis block micronucleus assay (CBMN assay) and b) telomerase activity (TA) in 23 mCRC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Numerous studies have shown that MN presence in certain populations of cWBCs are indicative of cancer presence and patients with worse clinical outcomes including in CRC, though the origin and specific subtype of these cells is unknown [ 11 , 17 ]. As CAMLs are a specific circulating stromal cell population that has been shown to be highly prognostic for patient outcomes [ 19 , 20 , 23 , 24 , 25 , 27 , 28 , 29 ], we evaluated the CAML population based on MN presence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that MN presence in certain populations of cWBCs are indicative of cancer presence and patients with worse clinical outcomes including in CRC, though the origin and specific subtype of these cells is unknown [ 11 , 17 ]. As CAMLs are a specific circulating stromal cell population that has been shown to be highly prognostic for patient outcomes [ 19 , 20 , 23 , 24 , 25 , 27 , 28 , 29 ], we evaluated the CAML population based on MN presence.…”
Section: Resultsmentioning
confidence: 99%
“…This is much lower than the rate of MN formation listed in prior publications, which averaged 61 MN per 186 baseline peripheral blood lymphocytes in CRC, and other solid tumor cancers [ 30 ]. However, this rarity is likely a result of the cancer specificity of CAMLs, which are an established cancer specific cWBC subtype, versus other groups studying MN formation with general blood lymphocytes which are more ubiquitous [ 11 , 17 , 19 , 27 , 30 , 31 ]. As MN presence has been previously associated with activation of the innate immune system, we examined the potential effects of MN formation on the number of CAMLs in circulation [ 16 , 20 , 21 , 29 ], finding no significant correlation between the presence of MN and the number of CAMLs found in circulation ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, it was found that the highest telomerase activity occurred ovarian, adrenal cortical, esophageal and lung cancer ( 54 ). In addition, it has been found that hTERT expression is increased in the early stages of colorectal cancer ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that micronuclei frequency (MNf) in peripheral blood lymphocytes may be a prognostic biomarker for monitoring the response of RC patients who undergo induction chemotherapy and then operation. However, it is not known whether MNf could also serve as a predictive biomarker of the response to chemoradiotherapy [126]. Other indexes based on changes to circulating lymphocytes have also been suggested as potential biomarkers of the response to nCRT.…”
Section: Circulating Lymphocyte Levelmentioning
confidence: 99%